Nutshell [book club bag] : a novel - McEwan, Ian (Nan A. Talese/Doubleday, 2016)
"Trudy has betrayed her husband, John. She's still in the marital home--a dilapidated, priceless London townhouse--but John's not here. Instead, she's with his brother, the profoundly banal Claude, and the two of them have a plan. But there is a witness to their plot: the inquisitive, nine-month-old resident of Trudy's womb. Told from a perspective unlike any other, Nutshell is a classic tale of murder and deceit from one of the world's master storytellers"--